Language Development in the Digital Age - Angelo Cangelosi; Giosue Baggio; Mila Vulchanova; Linda Smith (Frontiers Media SA, 2021)
The digital age is changing our children’s lives and childhood dramatically. New technologies transform the way people interact with each other, the way stories are shared and distributed, and the way reality is presented and perceived. Parents experience that toddlers can handle tablets and apps with a level of sophistication the children’s grandparents can only envy. The question of how the ecology of the child affects the acquisition of competencies and skills has been approached from different angles in different disciplines. In linguistics, psychology and neuroscience, the central question addressed concerns the specific role of exposure to language. Two influential types of theory have been proposed. On one view the capacity to learn language is hard-wired in the human brain: linguistic input is merely a trigger for language to develop. On an alternative view, language acquisition depends on the linguistic environment of the child, and specifically on language input provided through child-adult communication and interaction. The latter view further specifies that factors in situated interaction are crucial for language learning to take place. In the fields of information technology, artificial intelligence and robotics a current theme is to create robots that develop, as children do, and to establish how embodiment and interaction support language learning in these machines. In the field of human-machine interaction, research is investigating whether using a physical robot, rather than a virtual agent or a computer-based video, has a positive effect on language development. The Research Topic will address the following issues: - What are the methodological challenges faced by research on language acquisition in the digital age? - How should traditional theories and models of language acquisition be revised to account for the multimodal and multichannel nature of language learning in the digital age? - How should existing and future technologies be developed and transformed so as to be most beneficial for child language learning and cognition? - Can new technologies be tailored to support child growth, and most importantly, can they be designed in order to enhance specifically vulnerable children’s language learning environment and opportunities? - What kind of learning mechanisms are involved? - How can artificial intelligence and robotics technologies, as robot tutors, support language development? These questions and issues can only be addressed by means of an interdisciplinary approach that aims at developing new methods of data collection and analysis in cross-sectional and longitudinal perspectives. We welcome contributions addressing these questions from an interdisciplinary perspective both theoretically and empirically.